Ethical implications of artificial intelligence in nursing care: A systematic literature review from an Islamic perspective - Wan Mamat, Wan Hasliza; Mahat, Nur Ain; Zainudin, Airul Azizan; Mohamad Shariff, Nurasikin; Syed Elias, Sharifah Munirah; Salah, Machouche; Jamaludin, Maizatul Aisha; Merita Arini (Journal of Islamic, Social, Economics and Development, 2025)
While AI has significantly advanced patient care, clinical workflows, and medical research, there remains a lack of literature exploring AI’s ethical implications in nursing through the lens of Islamic values. This systematic literature review examines the ethical considerations of integrating artificial intelligence (AI) in nursing practice from an Islamic ethical perspective. The review synthesized documents published between 2014 and 2024, retrieved from Scopus, ProQuest, ClinicalKey for Nursing, and Google Scholar. The search followed PRISMA guidelines, and 19 eligible documents were included after screening. The synthesis identified three primary ethical themes: 1) Safety, with subthemes of data privacy, misuse, algorithm bias, and physical safety; 2) Human element, focusing on trust, empathy, and human touch; and 3) Autonomy and informed decision-making. Additionally, four key Islamic ethical concepts were identified: 1) Maqasid Al-Shariah (objectives of Islamic law), 2) Maslaha (public benefit), 3) Informed consent and liability, and 4) Text, understanding, and application (Nas, fiqh, and tabayyun). The findings highlight the importance of addressing the ethical challenges posed by AI in nursing, especially by providing adequate training for nursing professionals. Integrating Islamic perspectives into these discussions offers valuable insights that can enhance the ethical delivery of personalized, culturally sensitive, and efficient care. The review emphasizes the need for a nuanced approach to AI’s ethical implications in nursing practice, ensuring that AI’s potential is fully realized in an ethically grounded manner for diverse patient populations.